Application Of Modern Monetary Theory In Efforts For Country Economic Recovery From Islamic Economic Perspective - Putri, Mega Aulia; Pane, Erina; Irwantoni, Irwantoni (ASAS, 2024)
The global economic crisis is when all sectors of the world market economy experience a collapse (a state of emergency) and affect other sectors worldwide. To reduce the deficit, the DPR proposed money printing by observing the policies of several countries that carry out economic stimulus through printing money, as has been implemented by America and China, but the proposal from the DPR was rejected by the Ministry of Finance and BI because it was thought to cause inflation, but several countries in the eurozone have implemented MMT to be a solution to the economic crisis. Proponents of MMT argue that governments can print money to fund spending without causing inflation, as long as they manage the money supply and keep inflation rates low. This research aims to explain explicitly the application of MMT to improve the country's economy and how the concept of MMT is from an Islamic economic perspective. The method used in this article is qualitative library research. The study concludes that several countries, especially in Europe, have used the MMT concept to be applied to a country's economic development. Several pro-MMT experts explained that printing money will not result in inflation in the country as long as it manages the money supply and the inflation rate remains low, from an Islamic Economics perspective. Also, MMT is not contradictory because the MMT concept is something that humans use as a price standard, a means of exchange transactions, and a means of storage.Keywords: Economy; Inflation; Money;